Anti-carbon deposition mechanism of H2O on nickel-based anode of SOFC: A ReaxFF molecular modelling. (13th November 2020) - Wu, Sheng; Chen, Xintong; Jiang, Yunzhuo; Guo, Guanlun; Huang, Bin; Sun, Hui
Abstract: Carbon deposition occurs when Dimethyl ether (DME) fuel is used for SOFC, leading to battery degradation. In order to study the effect of water addition on carbon deposition, this work used reactive force field molecular dynamics (Reaxff MD) to simulate the process of carbon deposition with or without water addition, and analyze its anti-carbon deposition mechanism on nickel-based anode. It is found that the number of carbon atoms on nickel can be effectively reduced by mixing water with fuel. As the H2 O/DME ratio increases, there are fewer carbon atoms on the nickel anode. And there are two main ways for water molecules to resist carbon deposition. First is that the OH group generated by decomposition of water molecules at high temperature reacts with CH component to form aldehyde group, which reduces the formation of carbon deposition precursor. The other is that the increase of water molecules introduces more oxygen atoms into the system, and the carbon atoms formed by DME molecules combine with oxygen atoms to form CO, thus reducing carbon deposition. This study is helpful to promote the industrialization of DME as SOFC fuel. Highlights: The anti-carbon deposition mechanism of water is studied by ReaxFF MD. The carbon deposition can be effectively reduced by mixing water with fuel. The OH group reacts with CH component to reduce carbon deposition. The carbon atoms combine with oxygen atoms to reduce carbon deposition.